2020
DOI: 10.1108/lht-06-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the research progress of library and information science since the new century

Abstract: PurposeLibrary science and information science, two subdisciplines of library and information science (LIS), are developed independently but interconnectedly. In this information age, LIS is in a special period of transformation and development, which has caused some changes in both library science and information science. By accurately capturing these changes and analyzing them, the authors can effectively map the development of LIS in the new century, thus providing a reference for the evolution and developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Since 2012, artificial intelligence research has been expanding ( Hinton et al, 2012 ; Krizhevsky et al, 2012 ). Due to its advantages over geography and time constraints, this technology is considered a necessary resource for big data analysis ( Song et al, 2020 ). Particularly, in the field of education, a high-frequency artificial intelligence–related knowledge association has emerged, aiming to improve the efficiency of educational communication and to provide an assessment teaching system with distinct individual differences ( Tang et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2012, artificial intelligence research has been expanding ( Hinton et al, 2012 ; Krizhevsky et al, 2012 ). Due to its advantages over geography and time constraints, this technology is considered a necessary resource for big data analysis ( Song et al, 2020 ). Particularly, in the field of education, a high-frequency artificial intelligence–related knowledge association has emerged, aiming to improve the efficiency of educational communication and to provide an assessment teaching system with distinct individual differences ( Tang et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, an increasing number of researchers have been using various knowledge mapping tools to analyze the development trends and evolution processes of several disciplines. CiteSpace and VOSviewer are two major visualization tools in bibliometric research and other graphic science or scientific discipline research, both of which can import data directly from Web of Science and other bibliometric databases to generate visualizations ( Song et al, 2020 ). Comparing the differences between the two, VOSviewer is more accurate in clustering algorithms, while CiteSpace is better in presenting evolution and has the advantages of beautiful images and easier interpretation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers may also be interested in Hsiao and Chen (2021) about the continuance intention to use a food-ordering chatbot. Notably, CiteSpace is a common tool used by Song et al (2020) for analyzing LIS research articles, Zhao et al (2021) for psychological processing of contextual cues, Liu and Li (2021) for land use and carbon emissions and Feng et al (2022) for cultural and creative design.…”
Section: Studies On Science Researchmentioning
confidence: 99%
“…Sohaili et al (2016) examined the intellectual structure of research on information behavior during 2006-2014 using a co-word analysis. Song et al (2020) conducted a descriptor co-occurrence analysis and a burst analysis using CiteSpace to draw knowledge maps of LIS 2000-2019. They found that the focus of library science evolved from traditional to digital libraries and that of information science from information to data science.…”
Section: Related Studiesmentioning
confidence: 99%